Different Conceptions of Mental Illness: Consequences for the Association with Patients† - Helmchen, Hanfried (Frontiers in Psychology, 2013)
Whenever partial knowledge is considered absolute and turned into ideological and dogmatic conceptions, the risk increases that the conditions for the people involved might become dangerous. This will be illustrated by casuistic examples of consequences of one-sided psychiatric conceptions such as social, biological, and psychological ideas about the treatment and care of the mentally ill. Present perspectives of an integrative model, i.e. the bio-psycho-social conception about specific interactions between the social environment and individual characteristics on both the psychological and molecular-genetic level, require that all of these dimensions should be considered in order to personalize and thereby improve the care and treatment of the mentally ill.